2018
DOI: 10.3390/ijms19020360
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells: Cell Fate Decision to Osteoblast or Adipocyte and Application in Osteoporosis Treatment

Abstract: Osteoporosis is a progressive skeletal disease characterized by decreased bone mass and degraded bone microstructure, which leads to increased bone fragility and risks of bone fracture. Osteoporosis is generally age related and has become a major disease of the world. Uncovering the molecular mechanisms underlying osteoporosis and developing effective prevention and therapy methods has great significance for human health. Mesenchymal stem cells (MSCs) are multipotent cells capable of differentiating into osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
240
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(244 citation statements)
references
References 140 publications
(161 reference statements)
2
240
0
2
Order By: Relevance
“…Similarly, additional work is needed to clarify the impact of bone–muscle interactions on bone metabolism in response to various interventions, either pharmacological‐ or exercise‐based. Similarly, our findings suggest that bone‐regenerative capacity may be blunted in older individuals, as has been reported in the general population …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, additional work is needed to clarify the impact of bone–muscle interactions on bone metabolism in response to various interventions, either pharmacological‐ or exercise‐based. Similarly, our findings suggest that bone‐regenerative capacity may be blunted in older individuals, as has been reported in the general population …”
Section: Discussionsupporting
confidence: 89%
“…Similarly, our findings suggest that bone-regenerative capacity may be blunted in older individuals, as has been reported in the general population. (34)(35)(36) To our knowledge, this is the first study to detail the effects of combining bisphosphonate therapy with a bone-forming stimulus, such as FES-rowing, on bone following SCI. ZA is an antiresorptive therapy and FES-rowing is thought to be an osteogenic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The WNT signalling pathway regulates MSC maintenance, proliferation, fate determination and preadipocyte differentiation [13]. Additionally, it has been demonstrated that both canonical and noncanonical BMP signalling pathways are important in determining MSC differentiation [14]. It is thus essential to determine the expression of the components of these pathways in undifferentiated DPSCs.…”
Section: Introductionmentioning
confidence: 99%
“…adipocyte, lysophosphatidic acid receptor 4, osteoblast, ras homolog family member a, rhoassociated kinases 1, β-catenin 1 | INTRODUCTION As a common progenitor, the lineage commitment of mesenchymal stem cells (MSCs) plays an essential role in the maintenance of bone homeostasis. 1,2 Although MSCs are capable of differentiating into a variety of cell types, the competitive commitment of MSCs to adipocytes and osteoblasts has been specially concerned. 1,2 The imbalance between osteogenic and adipogenic differentiation is often found in many human diseases, such as osteoporosis and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although MSCs are capable of differentiating into a variety of cell types, the competitive commitment of MSCs to adipocytes and osteoblasts has been specially concerned. 1,2 The imbalance between osteogenic and adipogenic differentiation is often found in many human diseases, such as osteoporosis and obesity. 3,4 Therefore, it is important to elucidate the mechanisms that control the balance between osteoblasts and adipocytes.…”
Section: Introductionmentioning
confidence: 99%